Evidence for mitigation of coral bleaching by manganese. Issue 1 (December 2018) - Biscéré, Tom; Ferrier-Pagès, Christine; Gilbert, Antoine; Pichler, Thomas; Houlbrèque, Fanny
Abstract Unprecedented mass coral bleaching events due to global warming and overall seawater pollution have been observed worldwide over the last decades. Although metals are often considered as toxic substances for corals, some are essential at nanomolar concentrations for physiological processes such as photosynthesis and antioxidant defenses. This study was designed to elucidate, the individual and combined effects of nanomolar seawater enrichment in manganese (Mn) and iron (Fe), on the main physiological traits ofStylophora pistillata, maintained under normal growth and thermal stress conditions. We provide, for the first time, evidence that Mn is a key trace element for coral symbionts, enhancing cellular chlorophyll concentrations, photosynthetic efficiency and gross photosynthetic rates at ambient temperature. Our experiment also highlights the key role of Mn in increasing coral resistance to heat stress-induced bleaching. While Mn-enriched corals did not bleach and did not reduce their rates of photosynthesis and calcification, control corals experienced significant bleaching. On the contrary to Mn, Fe enrichment not only impaired calcification but induced significant bleaching. Such information is an important step towards a better understanding of the response of corals to seawater enrichment in metals. It can also explain, to some extent, species susceptibility to environmental stress.